Guidelines for Laboratory Diagnosis of Coronavirus Disease 2019 (COVID-19) in Korea - Hong, Ki Ho; Lee, Sang Won; Kim, Taek Soo; Huh, Hee Jae; Lee, Jaehyeon; Kim, So Yeon; Park, Jae Sun; Kim, Gab Jeong; Sung, Heungsup; Roh, Kyoung Ho; Kim, Jae Seok; Kim, Hyun Soo; et al. (Annals of laboratory medicine, 2020)
The outbreak of coronavirus disease 2019 (COVID-19), which began in December 2019, is still ongoing in Korea, with >9,000 confirmed cases as of March 25, 2020. COVID-19 is a severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection, and real-time reverse transcription-PCR is currently the most reliable diagnostic method for COVID-19 around the world. Korean Society for Laboratory Medicine and the Korea Centers for Disease Prevention and Control propose guidelines for diagnosing COVID-19 in clinical laboratories in Korea. These guidelines are based on other related domestic and international guidelines, as well as expert opinions and include the selection of test subjects, selection of specimens, diagnostic methods, interpretation of test results, and biosafety.